Corporate Social Responsibility Practices of Pharmaceutical Companies in China: A Scale Development Study - Qian, Y.; Reis, E.; Chen, C. (Corporate Responsibility Research Conference 2017, 2017)
Corporate Social Responsibility (CSR) has been a hot topic in literature ever since a couple of decades ago, and it roughly refers to the positive influence that a company’s operations have on its stakeholders. Amongst various industries, the pharmaceutical sector is one of the most debated in that these companies produce disease-curing and even life-saving products in a for-profit manner, thereby involving many CSR-related issues. Now China’s pharmaceutical industry has the second largest output in the world, but various problems have also emerged and led to negative consequences, many of which were caused by failure to abide by CSR norms. In order to assess the CSR practices of pharmaceutical companies in China, a reliable and credible measurement instrument has to be available. However, currently there is still no universally accepted definition of CSR, and existing theoretical models fail to fit either characteristics of the pharmaceutical industry or China’s cultural context. As a result, a new model has to be built that takes both factors into account. The main purpose of the study is to design an original and valid scale for measuring the CSR practices of pharmaceutical companies in China. Based on a standard scale development process (in-depth interviews, open-ended questionnaire, discussions with experts, reliability and validity evaluation with exploratory factor analysis), finally an eight-dimensional and 36-item measurement tool was validated. The eight initial dimensions (Shareholders, Managers, and Employees; Creditors & Suppliers, Patients & Doctors; Government, Environment, and Local Community) were then grouped together into three higher-order dimensions: CSR for Internal Parties, CSR for External Partners, and CSR for Public Entities. This scale has paved the way for future empirical study to further assess the CSR practices of pharmaceutical companies in China as well as other possibilities.